The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1124/jpet.115.227819
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin Promotes Non-rapid Eye Movement Sleep via Adenosine A1 Receptors

Abstract: Paeoniflorin (PF, C 23 H 28 O 11 ), one of the principal active ingredients of Paeonia Radix, exerts depressant effects on the central nervous system. We determined whether PF could modulate sleep behaviors and the mechanisms involved. Electroencephalogram and electromyogram recordings in mice showed that intraperitoneal PF administered at a dose of 25 or 50 mg/kg significantly shortened the sleep latency and increased the amount of non-rapid eye movement (NREM). Immunohistochemical study revealed that PF decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In the present study, we used whole-cell patch-clamp recordings to examine the effects of ethanol on neurons in slices prepared from the TMN in glutamic acid decarboxylase 67-green fluorescent protein (GAD67-GFP) knock-in mice. GAD67-GFP was used to identify histaminergic neurons because GAD67 is expressed in the histaminergic neurons in the TMN [18] . We found that ethanol suppressed the activity of histaminergic neurons in the TMN by directly hyperpolarizing the membrane potential and by potentiating GABAergic transmission mediated by GABA A receptors and under the tight regulation of GABA B autoreceptors.…”
Section: Original Articlementioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we used whole-cell patch-clamp recordings to examine the effects of ethanol on neurons in slices prepared from the TMN in glutamic acid decarboxylase 67-green fluorescent protein (GAD67-GFP) knock-in mice. GAD67-GFP was used to identify histaminergic neurons because GAD67 is expressed in the histaminergic neurons in the TMN [18] . We found that ethanol suppressed the activity of histaminergic neurons in the TMN by directly hyperpolarizing the membrane potential and by potentiating GABAergic transmission mediated by GABA A receptors and under the tight regulation of GABA B autoreceptors.…”
Section: Original Articlementioning
confidence: 99%
“…Male GAD67-GFP knock-in mice (weighing 16-20 g, 4-8 weeks old) in which GFP is expressed in GABAergic neurons under the control of the endogenous GAD67 promoter [18,19] were used for electrophysiological and immunohistochemical studies. Mice were maintained in the Laboratory Animal Center of Fudan University.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many pharmacological researches have reported liquiritigenin (GC12, 67.9%, 0.18), naringenin (GC16, 53.00%, 0.21), kaempferol (SY12, 42.06%, 0.24), and formononetin (GC6, 68.33%, 0.21) have many clinical indications, such as antidepressant-like effect [25, 26] and attenuating Alzheimer's-like learning in memory deficits [27, 28]. In addition, paeoniflorin (SY26, 32.07%, 0.40) has significant sedative effect, hypnotic effect, and promoting nonrapid eye movement sleep effect as the function of regulating sleep disorder [29, 30]. Then, we found that Licochalcone A (GC8, 42.78%, 0.29), Licochalcone B (GC27, 75.13%, 0.26), neohesperidin (ZS8, 61.75, 0.27), and glycyrrhizic acid (GC32, 31.78%, 0.55) which are contained in Radix Glycyrrhizae and Immature Bitter Orange have the anti-inflammatory and antioxidant function.…”
Section: Resultsmentioning
confidence: 99%